A fifteen‐year review of skin allergy testing in Irish patients with symptomatic rhinitis. Issue 4 (1st October 2021) - Nae, Andreea; Hinchion, K.; Keogh, I.J.
Abstract : Objective: Our objective was to review skin prick allergy testing (SPAT) results in patients with symptomatic rhinitis in an Irish population. Methods: A fifteen‐year retrospective review of our database of symptomatic patients with rhinitis was performed. All patients who had SPAT performed during this interval were included. Data was analysed in terms of demographics and dominant allergens. Results: 1158 patients were included. 617 Females vs 541 Males. Age range five to eighty‐five years old. Mean age thirty‐four years. 49% of our patients tested positive to at least one aeroallergen. The most common allergens were dust mites (23%) and timothy grass (22%). Patients born during the Irish pollen season (April–July) were between 5 and 7 times more likely to be sensitive to timothy and ryegrass pollens compared to others tested. 241 patients had both SPAT and serum allergen specific IgE testing (SASIgET) performed; positive results were consistent between both groups. Conclusion: Results demonstrated that half of our patients with symptomatic rhinitis had allergen sensitisation. Dust mites and grass were the main allergens in our area. Our nurse led clinic has allowed efficient patient education and the development of a unique Irish SPAT database. Retesting a patient with a known allergy test result it is not indicated.